Analisis Gender Longwe pada Program Desa Perempuan Indonesia Maju Mandiri di Desa Sumbersari Kabupaten Sleman - Fauzi Iqbal Hibatulloh; Tiyas Nur Haryani (Jurnal Mahasiswa Wacana Publik, 2023)
Women are a vulnerable group, victims of gender inequality. One form of women's vulnerability is women's poverty. Desa Perempuan Indonesia Maju Mandiri (Village PRIMA) is an example of a women's poverty alleviation program. PRIMA Sumbersari Village is the best PRIMA Village implementation in Sleman Regency. This study aims to determine the level of women's empowerment in the PRIMA Sumbersari Village program using the Longwe gender analysis tool. This research is a qualitative research, data collected through interviews, observations, and document studies. Data analysis using the Miles & Hubberman method. The results showed that five interesting levels were obtained. The level of welfare tends to be achieved. Members of PRIMA Sumbersari Village are able to increase their income, meet their daily needs, and have education funds from business proceeds developed with PRIMA Sumbersari Village. The level of access tends to be strongly achieved. PRIMA Sumbersari Village members have and utilize access to income and training resources. The level of awareness tends to be weak because not all members have received education about gender. Participation rates tend to be weakly achieved. PRIMA Village members have actively participated in various PRIMA Village activities at various levels, but have not been active in formulating policies at the regional level. The level of control tends to be strong enough to achieve. PRIMA Sumbersari Village members have control over their production factors and business income.